Police interrogator: a helping profession? - Ptácek, Radek (SIAK-Journal, 2006)
Interview is the most frequent investigative stage, which, in fact, cannot be omitted in any crime investigation. While the legal and criminal approach focuses on content, tactical and process features, the psychological approach aims at the understanding and development of the interpersonal, relational feature of the interview interaction. It appears that effective interview interaction can be spoken about when,except for quantitative criterium, ie gathering and documenting a necessary amount of legally relevant information, we accept psychological, ie qualitative features performed by an extent of social satisfaction of participants in the interview interaction. The interview interaction particularly depends upon the interviewer's abilities and skills to establish, keep and develop psychological contact. Establishing psychological contact depends on the interviewer's perception and emotional experience of the interview interaction (especially behaviour and responses of interviewees or other people, and conditions under which a particular interview interaction takes place), and on how this experience is reflected in the attitudes towards the interviewee, the interview and the interviewer him/herself. The research is aimed at grasping the specifics of interpersonal relationships, at mapping the factors which influence these relationships, and at finding the presence of attitudes which facilitate establishing psychological contact in the course of the interview.